Factor analysis on spur gear failure using computational simulation / Emilia Norazmi - Emilia, Norazmi (2021)
Spur gears are purported to be the most well-known and simplest gear as compared to other type of gears. Spur gears are also said to be regularly used in series to avoid from using massive size gear. The utilisation of spur gears is basically to shift movement from one shaft (tube) to another shaft that are similar or parallel. Due to deemed as the simplest gears of all gears, spur gears hence are widely applied in most of daily utilised devices and machine such as clocks, washing machines, blenders, kitchen mixers and even music equipment i.e. musical box. To ensure that the musical box can operate and emit a melodious and soothing sound, spur gears are one of the main components in it. Nevertheless, the musical box is criticised to be easily damaged, and the damage is often caused by the destruction of the spur gears encompass the device. In lieu of that, this study will involve the study of spur gears in the musical box that is intended to fill the literature gap. It is hoped that the findings and results from this study can contribute new knowledge in the field of mechanical, specifically on the mechanism of the spur gear. Apart from that, it is also hoped that the result from this study will be able to draw the baseline information on the effect of stress on spur gears towards the performance of the musical box.